The return of the dispersed metal waste into production - S. L Rovin; A. S. Kalinichenko; L. E. Rovin (Литьë и металлургия)
The article presents an alternative method of recycling of dispersed metal waste, based on a continuous solid-liquid-phase process, implemented in rotary tilting furnaces (RTF). The new proposed method of recycling allows processing wastes with almost any composition and state from metal to oxide and multicomponent wastes (shavings, fine scrap, mill scale, aspiration dust, sludge, etc.). The wastes can be even contaminated with moisture, oil, and organic impurities. The method developed does not require preliminary preparation of the initial materials (cleaning, homogenization, pelletizing, etc.). The finished products are ingots (pigs) for subsequent processing aiming the particular chemical composition or cast alloys of certain brend.